Risk of aortic aneurysm or dissection in autosomal dominant polycystic kidney disease : systematic review and meta-analysis - Nunes, Raquel Filipa Costa Pascoal (2022)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2021